Expression of cell cycle control proteins in normal epithelium, premalignant and malignant lesions of oral cavity - Shintani, Satoru; Mihara, Mariko; Nakahara, Yuji; Kiyota, Akihisa; Ueyama, Yoshiya; Matsumura, Tomohiro; Wong, David T.W (Oral oncology, 2002)
In this study, we examined the expression of cyclins, cyclin dependent kinase (CDKs) and CDK inhibitors by immunohistochemical analysis in 20 normal mucosa, 42 epithelial dysplasia (ED), and 117 oral squamous cell carcinoma. Neither Cyclin D1 nor CDK2 were detectable in normal tissue and ED. Their presence, however, was detectable in squamous cell carcinoma (SCCs) (Cyclin D1, 35.9%; CDK2, 66.7%). Cyclin E was detectable in 57.1% of severe ED and 62.8% of SCCs. For the CDK inhibitors, these proteins were detectable in all normal mucosa and most of the mild and moderate ED. For severe ED, expression of these proteins was not observed in some cases (p12 DOC−1, 14.3%; p16 INK4A, 28.6%; p27 KIP1, 7.1%). For SCCs, the expression of p12 DOC−1 was lost in 71.8%, p16 INK4A in 69.2% and p27 KIP1 in 35.9%. These results suggest that elevated expression of cyclin D1, cyclin E, CDK2 and loss of p12 DOC−1, p16 INK4A and p27 KIP1 may contribute to the multistep nature of oral carcinogenesis.